Connecticut’s juvenile review boards: a piece of the puzzle in restorative front-end diversion efforts - Garrett, DayQuan (Contemporary justice review, 2024)
As youth engage in behaviors that have been designated delinquent and criminal, there is a need to provide them discipline without requiring them to become justice-involved. In Connecticut, Juvenile Review Boards (JRBs) use restorative practices integrated into front-end diversions to create an opportunity for service providers to relationally serve youth, their families, and the broader community. This study shares findings from focus groups inductively reviewed for themes. Emphasizing thoughtful strategies, the participants detailed their journey to prevent youth from unnecessary system contact and provide the appropriate level of services to address any unmet needs that prompted the discouraged behavior.